Case Report: A case of cutaneous collagenous vasculopathy - Chenjian Tang; Liping Chen; Jiangxiu Yu; Mei Zhu (Frontiers in Medicine, 2026)
We report a case of a 62-year-old woman presenting with a 6-year history of purpuric patches and macules on the lower extremities, initially misdiagnosed as allergic purpura and treated with prednisone. Skin biopsy revealed dilated dermal vessels with perivascular collagen deposition, positive for collagen IV and diastase–periodic acid–Schiff (D-PAS) staining, consistent with cutaneous collagenous vasculopathy (CCV). Treatment included hydroxychloroquine, vitamin C, doxepin, and topical mucopolysaccharide polysulfate cream. Prednisone was tapered by one tablet every 3 days. After 4 weeks, the rash improved significantly with no new lesions. We would like to present a case of CCV.